Self-Regulated Learning on ChatGPT in Writing Theses for Master Degree Students in Higher Education - Alni Nur Firani; Murti Kusuma Wirasti; Murni winarsih (Journal of Science and Education (JSE), 2026)
In today's digital age, the advent of artificial intelligence technology provides an alternative for master's programme students in writing their theses. However, there are still students who find it difficult to use AI technologies such as ChatGPT in writing their theses. Therefore, this study aims to analyse the needs of master's programme students in writing their theses with the help of ChatGPT. This study uses a descriptive qualitative approach. The participants in this study were 10 master's students in educational technology who were in the process of writing their theses. Participatory observation and in-depth interviews were the data collection techniques used by the researcher. In addition, the data analysis techniques used were reduction, data presentation, and drawing conclusions. The results of this study indicate that master's programme students still need guidance in writing their theses through ChatGPT. This is because ChatGPT guidance can provide students with directions to minimise plagiarism and serve as a supporting tool for thesis writing. This guidance is not limited to face-to-face meetings but also includes guidance that can be used independently. Thus, self-regulated learning on ChatGPT can be an alternative for second-year master's programme students. With self-regulated learning on ChatGPT, students are expected to be able to manage an independent, focused, and continuous learning process in writing their theses.